Cultural code: video games and Latin America - Penix-Tadsen, Phillip (The MIT Press, 2016)
How culture uses games and how games use culture: an examination of Latin America's gaming practices and the representation of the region's cultures in games. Video games are becoming an ever more ubiquitous element of daily life, played by millions on devices that range from smart phones to desktop computers. An examination of this phenomenon reveals that video games are increasingly being converted into cultural currency. For video game designers, culture is a resource that can be incorporated into games; for players, local gaming practices and specific social contexts can affect their playing experiences. In Cultural Code, Phillip Penix-Tadsen shows how culture uses games and how games use culture, looking at examples related to Latin America. Both static code and subjective play have been shown to contribute to the meaning of games; Penix-Tadsen introduces culture as a third level of creating meaning. Penix-Tadsen focuses first on how culture uses games, looking at the diverse practices of play in Latin America, the ideological and intellectual uses of games, and the creative and economic possibilities opened up by video games in Latin America—the evolution of regional game design and development. Examining how games use culture, Penix-Tadsen discusses in-game cultural representations of Latin America in a range of popular titles (pointing out, for example, appearances of Rio de Janeiro's Christ the Redeemer statue in games from Call of Duty to the tourism-promoting Brasil Quest). He analyzes this through semiotics, the signifying systems of video games and the specific signifiers of Latin American culture; space, how culture is incorporated into different types of game environments; and simulation, the ways that cultural meaning is conveyed procedurally and algorithmically through gameplay mechanics. Source: Publisher
Section: ix, 333 pages : illustrations ; 24 cm.
Keywords: 1-Jeux vidéo; 2-Analyses formalistes; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

On Video Games: the Visual Politics of Race, Gender and Space - Murray, Soraya (I.B. Tauris & Co. Ltd., 2018)
Today over half of all American households own a dedicated game console and gaming industry profits trump those of the film industry worldwide. In this book, Soraya Murray moves past the technical discussions of games and offers a fresh and incisive look at their cultural dimensions. She critically explores blockbusters likeThe Last of Us, Metal Gear Solid, Spec Ops: The Line, Tomb Raider and Assassin's Creed to show how they are deeply entangled with American ideological positions and contemporary political, cultural and economic conflicts.As quintessential forms of visual material in the twenty-first century, mainstream games both mirror and spur larger societal fears, hopes and dreams, and even address complex struggles for recognition. This book examines both their elaborately constructed characters and densely layered worlds, whose social and environmental landscapes reflect ideas about gender, race, globalisation and urban life. In this emerging field of study, Murray provides novel theoretical approaches to discussing games and playable media as culture. Demonstrating that games are at the frontline of power relations, she reimagines how we see them - and more importantly how we understand them.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé

Video Games Around the World - Wolf, Mark J. P. (MIT Press, 2015)
Video games have become a global industry, and their history spans dozens of national industries where foreign imports compete with domestic productions, legitimate industry contends with piracy, and national identity faces the global marketplace. This volume describes video game history and culture across every continent, with essays covering areas as disparate and far-flung as Argentina and Thailand, Hungary and Indonesia, Iran and Ireland.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; _Nettoyé

Gaming Globally: Production, Play, and Place - Huntemann, Nina B.; Aslinger, Ben (Palgrave Macmillan, 2013)
Video games are inherently transnational by virtue of their industrial, textual, and player practices. This collection includes essays from scholars from eight countries analyzing game cultures on macro- and micro-levels and investigates the growing transnational nature of digital play
Section: xi, 279 p. : ill. ; 23 cm.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé